Building Community Resilience Through Collaboration with Government in Flood Preparedness in Lahat District, South Sumatra - Febriyanti, Doris; Aqilah, Fatin Nada; Amaliatulwalidain, Amaliatulwalidain; Kusuma, Rosy Riani; Khotsing, Thannaphat (Universitas Teuku Umar, 2025)
Floods are a major threat worldwide, including in Lahat Regency, South Sumatra, where heavy rains and overflowing Lematang River often cause severe flooding. The Lahat Regency Government plays a key role in disaster response, but places more emphasis on post-disaster recovery than preparedness. There is limited research on how organizations collaborate in disaster management, especially in a developing country like Indonesia. This study addresses this gap by examining organizational collaboration across different stages of disaster management in Lahat Regency during 2023. The objectives of this study were to analyze the mechanisms of inter-organizational collaboration in flood management, identify challenges faced in early warning systems and aid distribution, and explore potential for improved coordination between provincial and district-level organizations. Using exploratory qualitative methods, the researchers analyzed flood preparedness and response based on the experiences of government officials, NGOs, and KBBM. Data were collected through semi-structured interviews, coded thematically, and validated through source triangulation. The findings highlight the importance of a proactive approach and shared responsibility, especially for communities affected by floods. The government faces challenges in early warning systems and aid delivery due to communication gaps. However, coordination between provincial and district-level organizations in South Sumatra has the potential to improve disaster management through improved information sharing and resource distribution. This study contributes to the understanding of disaster cooperation networks and underscores the need to strengthen collaboration and preparedness efforts.